1999
DOI: 10.1177/0145482x9909301003
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Instrument to Measure Manual Dexterity in Children with Visual Impairments Aged 6–12

Abstract: This article describes the development of the Test for Manual Dexterity in Visually Impaired Children. The test was used to chart the manual skills of children with visual impairments (those who were blind or had low vision) and a control group of sighted children in the Netherlands and to compare the development of children who were blind or had low vision.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 9 publications
0
16
0
Order By: Relevance
“…This delay often results in low body awareness, deficits in manual operations, as well as deficits in the two-handed object manipulation (Brambring, 2007;Jan et al, 1990). Problems in the area of bilateral coordination can have an important influence on mastering more complex motor skills (Brambring, 2007;Houwen, Visscher, Hartman, & Lemmink, 2007;Houwen et al, 2008;Reimer et al, 1999). Bouchard and Tetreault (2000) found that children with severe visual impairment mastered motor skills later than sighted children.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This delay often results in low body awareness, deficits in manual operations, as well as deficits in the two-handed object manipulation (Brambring, 2007;Jan et al, 1990). Problems in the area of bilateral coordination can have an important influence on mastering more complex motor skills (Brambring, 2007;Houwen, Visscher, Hartman, & Lemmink, 2007;Houwen et al, 2008;Reimer et al, 1999). Bouchard and Tetreault (2000) found that children with severe visual impairment mastered motor skills later than sighted children.…”
Section: Discussionmentioning
confidence: 99%
“…The analysis of motor skills and the diagnosis of children with visual impairment, especially of children with blindness, are more complex than for their sighted peers; thus, the available research on this topic is limited. Some studies have indicated that the level of motor skills in children and young people who are blind and visually impaired is lower than in their sighted peers (Atasavun Uysal & Dulge, 2011;Bouchard & Tetrault, 2000;Brambring, 2007;Houwen, Visscher, Lemmnik, & Hartman, 2008;Reimer et al, 1999). However, other studies have indicated that the development of compensatory mechanisms in children with visual impairment allowed children with partial sight and blindness to achieve outcomes on some coordination tests similar to those of their able-bodied peers (Navarro et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…5,6 Earlier studies have shown that children with VI generally have lower motor performance than their peers without VI, but also that some motor tasks are a more difficult than others. [7][8][9] However, as previous studies have either focused on a subset of motor skills 8,9 (e.g. manual dexterity) or have compared motor skill areas 7 (e.g.…”
mentioning
confidence: 99%
“…13 Although studies showed primarily that some residual vision is facilitative for motor performance, 7,14,15 there are also examples where children with more residual vision do not necessarily perform better than children with little or no vision. 8 Furthermore, the majority of previous research on the effect of the degree of VI has primarily focused on blind children versus children with residual vision, 9,16 making it difficult to conclude in which way different degrees of VI are associated with motor performance.…”
mentioning
confidence: 99%
See 1 more Smart Citation